1975
DOI: 10.1111/j.1432-1033.1975.tb02367.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mannosylation of Dolichol‐Diphosphate Oligosaccharides in Relation to the Formation of Oligosaccharides and Glycoproteins in Pig‐Liver Endoplasmic Reticulum

Abstract: In the chain-lengthening of the oligosaccharide chains of endogenous dolichol-diphosphate oligosaccharides (Dol-P-P-oligosaccharides) by a pig liver microsomal preparation dolicholmonophosphate mannose (Dol-P-Man) was a more efficient donor of mannose (a maximum of 35 SC transferred by 5 min) than was GDP-Man (reaching 16 7; by 45 min). The effects of an excess of GDP, an excess of GDP-Man, a lack of Mn" and an excess of EDTA showed that the transfer from GDP-Man was via Dol-P-Man. The evidence also indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…4) (Table I) produced by the particulate fractions from GDP-mannose or UDP-GlcNAc supports this concept. Lipid-linked oligosaccharides have been implicated as precursors of the glycosyl component of glycoproteins (14,20,21). The time course kinetic data ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4) (Table I) produced by the particulate fractions from GDP-mannose or UDP-GlcNAc supports this concept. Lipid-linked oligosaccharides have been implicated as precursors of the glycosyl component of glycoproteins (14,20,21). The time course kinetic data ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier repots have indicated a preferential stimulatory effect by Mg24 and Mn2" on the transfer of radioactivity from GDP-[14CJMan2 to lipid intermediates and glycoproteins (4,12,13,15,18,21). In contrast, very little information is available on the divalent cation effect on UDP-[14C]-GlcNAc transferase activities.…”
mentioning
confidence: 99%
“…Earlier repots have indicated a preferential stimulatory effect by Mg24 and Mn2" on the transfer of radioactivity from GDP-[14CJMan2 to lipid intermediates and glycoproteins (4,12,13,15,18,21 nucleoside diphosphate sugars are given below. Incubation was at 37 C for 60 min with the reaction terminated by the addition of 0.7 ml of H20 and 2.5 ml of chloroform-methanol (2:1, v/v).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been found that, during the N-glycosylation of proteins in the ER, a significant number of unconjugated, free oligosaccharides (free OSs) are formed (7)(8)(9). The occurrence of free OSs has been reported in a wide variety of cells (10)(11)(12)(13)(14), and their sequential processing event of free OSs in mammalian cells has also been well characterized (15)(16)(17)(18)(19). When the free OSs are formed in the lumen of the ER, they are transported out of the ER to the cytosol (15).…”
mentioning
confidence: 99%